The Effect of BI Rate and Inflation on Mudharabah Deposits at Indonesian Sharia Banks - Ika Safitri; Muhamad Rizal Kurnia (Journal of Business and Economics Research (JBE), 2022)
Even though Islamic banking is running its sharia-based business activities, it is inseparable from macroeconomic developments, namely fluctuations in inflation and BI rate (interest rates) in 2015-2020. This study aims to analyze and determine the effect of BI Rate and Inflation on Mudharabah Deposits at Indonesian Islamic Banks (2015-2020 Period). The research method used is a quantitative method. The data used is secondary data in the form of complete financial reports for the 2015-2020 period with a total of 72 data. In the research population, there are 14 Islamic Commercial Banks (BUS) and the sample used is 3 Islamic Bank companies which become one entity, namely Bank Syariah Indonesia. The analytical tool used is multiple linear regression analysis which is tested with the Eviews 10 program. The results of this study indicate that partially the BI Rate has a negative and significant effect on Mudharabah Deposits, partially Inflation has a negative and significant effect on Mudharabah Deposits. Meanwhile, the BI Rate and Inflation simultaneously have a negative and significant effect on Mudharabah Deposits.